Silver Nanoparticles: A Versatile Tool Against Infectious and Non-Infectious Diseases - Sara González-Fernández; Noelia Blanco-Agudín; David Rodríguez; Iván Fernández-Vega; Jesús Merayo-Lloves; Luis M. Quirós (Antibiotics)
Silver nanoparticles possess remarkable properties that render them highly beneficial for medical applications in both infectious and non-infectious diseases. Among their most renowned attributes is their antimicrobial activity. They have demonstrated efficacy against a wide range of bacteria, fungi, protozoa, and viruses. Additionally, the antitumor and anti-diabetic properties of silver nanoparticles, along with their ability to promote wound healing and their application as biosensors, underscore their therapeutic potential for various non-infectious conditions. As silver nanoparticles are employed for medical purposes, their potential toxicity must be considered. While silver nanoparticles present a promising alternative in the therapeutic domain, further research is needed to elucidate their precise mechanisms of action, optimize their efficacy, and mitigate any potential health risks associated with their use.